Effect of managing technical risk towards reducing cost of production in project - Mohd Amerul Amin, Razali (2014)
In world life today, there are always risks. In a project, the risk will become the strongest obstacle to ensure the project is successful which means it meets the goal without affecting the cost. Risks that appear in projects will affect the cost directly and usually will result in cost overrun. This study focuses on the cost for production which is also an important factor to be managed in a project. This study aims to reduce the production cost for project without affecting the scope and quality of the project. A company is impossible to reduce the cost through cutting in the material being used because it can directly affect the quality. Therefore, the objective of this study is to find whether by managing technical risks according to project phases, the production cost can be reduced. Statistical Package for Social Science (SPSS) software has been used to find the linear regression and Pearson correlation of the questionnaire imposed. The outcome shows that in execution phase, wrong in cost estimation risk is the most important to be managed to reduce the cost, while in planning phase, the environmental risk and operation risk are the most important to be managed to reduce the cost. In future, it is suggested that a comparison is made between two or more company in getting more accurate result and in analyzing the exact value for cost in a sample project. As the conclusion, project managers should focus to manage those risks that have strong relationship to ensure that they can reduce the cost of production in order to maintain the project scope and quality.